Psikoedukasi tentang Bahaya Penyalahgunaan Narkoba dan Peningkatan Self Awarness di Sebuah Komunitas - Rachmaputri, Nimas Bunga; Rosyidi, Hamim; Andiarna, Funsu (Journal Pemberdayaan Masyarakat Indonesia, 2025)
The drug problem in Indonesia is still something that is urgent and complex. This problem is becoming widespread as evidenced by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of drug crime cases with increasingly diverse patterns. The impact of drug abuse not only threatens the survival and future of the abuser, but also the future of the nation and state. Until now, the level of drug trafficking has reached various levels, not only among adults but also among teenagers. Therefore, it is very important to build self-awareness in teenagers as the initial foundation for applying moral values ​​in everyday life. This empowerment uses psychoeducational methods with subjects of 25 students from the Saka Bakti Husada Community, Benowo Pangkalan Dr. Community Health Center. Lubis Protection